2022
DOI: 10.1038/s41598-022-17227-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between antithrombin administration and inflammation during veno-venous ECMO

Abstract: Veno-venous Extracorporeal Membrane Oxygenation (ECMO) is used in the most severe cases of respiratory failure and further exacerbates the patients’ inflammatory status. Antithrombin is supplemented during ECMO for its anticoagulant effects, but it also deploys anti-inflammatory properties. In this pre-specified ancillary study of the GATRA trial [NCT03208270] we aimed to evaluate the relationship between antithrombin and inflammation during ECMO. Forty-six patients were included in the study, 23 were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Some adult studies also suggest that AT3 could reduce inflammation. 28 Further studies in children are needed to evaluate the potential benefits of AT3 supplementation. 13,16,19 While the clinical benefits of AT3 administration are unclear, the financial costs are evident.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some adult studies also suggest that AT3 could reduce inflammation. 28 Further studies in children are needed to evaluate the potential benefits of AT3 supplementation. 13,16,19 While the clinical benefits of AT3 administration are unclear, the financial costs are evident.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that once a validated age‐specific AT3 target is identified (e.g., ≥50%), AT3 supplementation could improve patient outcomes. Some adult studies also suggest that AT3 could reduce inflammation 28 . Further studies in children are needed to evaluate the potential benefits of AT3 supplementation 13,16,19 …”
Section: Discussionmentioning
confidence: 99%
“…Primary outcome results have not yet been published, but a pre-specified ancillary study showed a correlation between AT therapy and a decrease in inflammatory cytokines. 83 Overall, prevention of thrombosis must be balanced with efforts to minimize risks of bleeding, which can be particularly high in neonatal and pediatric patients. In both pediatric and adult patients undergoing ECMO or similar mechanical circulatory support such as a ventricular assist device, it can be a challenge to achieve appropriate titration of anticoagulation to prevent hemorrhagic and/or thrombotic complications, especially as substantial variability exists in the approach to management of anticoagulation and antiplatelet therapy.…”
Section: Patients Undergoing Ecmomentioning
confidence: 99%
“…Primary outcome results have not yet been published, but a pre-specified ancillary study showed a correlation between AT therapy and a decrease in inflammatory cytokines. 83…”
Section: Additional Patient Populations and Use Cases Where At Therap...mentioning
confidence: 99%
“…In a recent sub-study of a multicenter randomized trial assessing the effect of antithrombin (AT) supplementation during vv-ECMO, 3 we observed that AT administration was associated with reduced plasmatic levels of pro-inflammatory cytokine. 14 This suggests that AT does not only play as the serine-protease cofactor of heparin for its anticoagulant properties, but it also deploys anti-inflammatory and anti-microbial properties. 15,16 The effects of circulating inflammatory cytokines on viscoelastic test parameters during vv-ECMO are unknown.…”
Section: Introductionmentioning
confidence: 99%